Using Selected Structural Indices to Pinpoint the Field Moisture Capacity of Some Coarse-Textured Agricultural Soils in Southeastern Nigeria - Igwe, Charles Arizechukwu; Hermansah, .; Obi, Martin Eze; Wakatsuki, Toshiyuki (JOURNAL OF TROPICAL SOILS, 2011)
Over- or underestimation of field capacity (FC) of agricultural soils could misguide soil and water management and this might have negative agronomic and environmental impacts. The study sought to identify the moisture tension for reliably estimating in the laboratory the FC of some sandy soils with low-activity clay minerals and at different levels of structure development in Nsukka agroecological zone in southeastern Nigeria. Fifty-four samples of topand subsoils under contrasting vegetation cover at three locations in the zone were analyzed for texture, organicmatter contents, bulk density and total porosity. Saturated hydraulic conductivities (Ksat) of the samples were equallydetermined. Water-conducting and water-filled porosities at each of 0.06-, 0.10- and 0.33-bar tensions were implied from water retention data at the respective tensions. The soils were categorized based on their levels of structure development using a structural stability index [(organic matter: silt+clay) %] as follows: very low (< 4%), low (4-7.5%) and moderate to high (> 7.5%) stability soils. Series of simple correlation tests were run among the waterconducting porosities at the various tensions and the Ksat of the soils. In each case, the soil was assumed to have attained FC at that moisture tension which the associated water-conducting porosity showed significant positive correlation with the Ksat. Our results revealed that the 0.06-bar tension overestimated the FC of the soils. The 0.10-bar tension, the commonly used moisture tension for the purpose in the study area, proved suitable only for soils within the moderate to high structural stability category. From all indications, the 0.33-bar tension best corresponded to the FC of the less structurally developed soils in the other two categories. The level of soil structure development should therefore be considered before deciding the suitable moisture tension for the determination of FC of these and similar soils in other tropical locations.Keywords: Coarse mineral soils, field moisture capacity, saturated hydraulic conductivity, structural stability,water-conducting pores